Brazilian Jiu Jitsu: Considerations for strength and conditioning training plan design. - Yates, J. M. P. (Journal of Australian Strength and Conditioning, 2017)
Currently there are few articles that concentrate specifically on the sport of Brazilian Jiu Jitsu (BJJ) when compared to other grappling sports. However, the requirements of a BJJ athlete may be different that of an athlete competing in another grappling sport, such as wrestling or judo. This article discusses various training considerations that must be taken into account when designing BJJ specific training plans. The aim is to provide the BJJ coach or athlete whom may have little prior strength and conditioning experience with a guideline for planning and implementing an effective strength and conditioning program. These points are based on a needs analysis of BJJ. An analysis of current literature was performed focusing on strength and conditioning for grappling sports. The needs analysis is based on physiological and technical/tactical data from the sport which may help the reader to better understand the components of fitness required for success in BJJ. Strength and conditioning programmes for BJJ athletes should involve resistance, plyometric and aerobic/anaerobic energy system training. A template for strength exercises is offered, categorizing each movement to allow them to be integrated into training for the most effective result. Examples of strength training and metabolic conditioning sessions are also provided so that a coach or athlete may see a visual representation of how to plan the session. The training considerations provide an athlete or coach with the necessary information to allow them to develop an appropriate training plan to aid athletic development and facilitate successful performance in BJJ competition.